Sensory and analytical impacts of unmalted cereal adjunct usage in lager brewing - Yorke, Joanna (2022)
The use of unmalted cereal adjuncts (barley, wheat, rice and maize) is well established in the brewing industry, with typical incorporation rates of up to 30%. Unmalted cereal adjuncts are utilised in the production of light lager beers to provide cost and energy reductions and as a response to consumer demand for a lighter beer style. However, there is little comprehensive data concerning the sensory and analytical impacts of using high proportions of unmalted cereal adjuncts. This was the context to the main objectives of this PhD research: to better understand the sensory characteristics and consumer perception of beers produced with unmalted adjuncts and develop protocols to improve flavour matching to all-malt counterparts. The sensorial and analytical profile of lager beers produced with relatively high concentrations (0, 30 and 60% of grist) of unmalted barley, wheat, rice and maize and an all-malt control were determined (Chapter 3). A trained sensory panel developed and defined an adjunct beer lexicon which was used to characterise the sensory properties of the beers. Results from the sensory evaluation showed that at 30% adjunct incorporation there was insignificant variation in the beer flavour profiles (p>0.05). Whereas, at 60% adjunct incorporation there were some significant sensory differences identified that were specific to particular adjunct materials. Furthermore, high adjunct incorporation significantly decreased wort free amino nitrogen (FAN) which impacted the fermentation volatile profile corresponding to specific characteristics in the sensory analysis. In Chapter 4 two different approaches were investigated to enhance free amino nitrogen when brewing with high incorporations of unmalted cereal adjuncts: i) addition of exogenous thermostable proteolytic enzymes during mashing and ii) additions of yeast nutrients to the cold wort before fermentation. Beer samples produced with unmalted wheat and two types of unmalted barley at different grist proportions (15, 25, 35 and 45%) were supplemented by these two approaches to achieve a FAN concentration greater than 200 mg/L. Increasing the wort FAN concentration of adjunct beers was shown to improve the fermentation volatile profile consistency relative to an all-malt control; decreasing variation in ester and higher alcohol concentrations to less than 20% from control for all adjunct beers. The results of this work suggest that by balancing wort composition the analytical flavour profile of a full malt beer could be more closely matched such that flavour may not be a limiting factor at higher levels of unmalted adjunct usage. In Chapter 5, a sample set of 7 adjunct beers produced with unmalted cereal adjuncts up to 45% were assessed alongside an all-malt control lager by consumers (n=104). The consumers assessed beers for hedonic liking (to determine consumer acceptance) and purchase intent. Overall, adjunct beers produced with FAN boost supplementation were not significantly different in overall liking and purchase intent compared to the all-malt control (p>0.05). In terms of liking, three clusters of consumers were discovered with different patterns of preference, revealing that consumers are not consistent in their preference when considering adjunct based beers. Interestingly, it was found that one cluster (24% of consumers) had a preference for high adjunct beers. A Check-All-That-Apply (CATA) technique was used to determine consumer sensory perception of the beers. The combination of CATA and overall liking data provided key sensory liking and disliking drivers to guide future improvement of lager beers brewed with higher adjuncts rates. ‘Malty’, ‘apple’, ‘sweet’ attributes were all significant positive drivers for liking and ‘lingering bitterness’ was the only significant negative driver for liking (p<0.05). Consumers used terms such as ‘refreshing’, ‘light’ and ‘weak flavour’ to describe the beers which were not in the CATA lexicon determined by the trained panel, signifying the different language consumers use to define the product. In Chapter 6, a non-targeted metabolomics approach was used to determine non-volatile metabolites which could contribute to flavour differences observed when brewing with unmalted barley. Ultra-high performance liquid chromatography (UHPLC) couple to a quadrupole time-of-flight mass spectrometer with an electro-spray ionisation source (ESI) was used to analyse three beer samples (100% malt and two 15% unmalted barley beers). The metabolomic profile of the three beers were compared using principal component analysis (PCA) to determine significantly different molecular features. Results found that the main differential molecular features were nitrogenous peptides and purine derivatives. This result can be attributed to the lack of malting process and thus lack of proteolytic enzyme activity being applied to the proportion of unmalted barley, reducing the protein and peptide breakdown of the unmalted barley. Several of the differential peptides identified had amino acid residues which are known for causing bitter and kokumi taste in beer, which could attribute to the bitterness observed when brewing with unmalted barley. Overall, this work has shown that the use of unmalted adjuncts at higher incorporation rates has fewer direct flavour impacts than was anticipated, provided that steps were taking to maintain the wort composition. The main sensory differences noted at high adjunct rates were lack of fullness and development of lingering bitterness and astringency. Interestingly, consumer data showed that there are consumers who actually prefer high adjunct beers. However, if the aim were to flavour match as closely as possible to an all-malt beer, the metabolomics study in Chapter 6 provides new metabolite targets and hypotheses which can be used to improve flavour matching.